Effect of Glutathione on Sperm Quality in Guanzhong Dairy Goat Sperm During Cryopreservation - Zou, Jiahao; Wei, Lixuan; Li, Dexian; Zhang, Yongtao; Wang, Guang; Zhang, Lei; Cao, Ping; Yang, Shaohua; Li, Guang (Frontiers in Veterinary Science, 2021)
In the process of cryopreservation of dairy goat semen, it will face many threats such as oxidative damage, which will affect the motility and plasma membrane function of sperm. As an endogenous antioxidant in animals, glutathione(GSH) can significantly improve the quality of thawed sperm when added to the frozen diluent of semen of pigs and cattle. In this study, different concentration gradients of GSH[0mmol/L(control), 1mmol/L, 2mmol/L, 3mmol/L, 4mmol/L] were added to the frozen diluent of Guanzhong dairy goat semen. By detecting the sperm motility parameters, acrosome intact rate and plasma membrane intact rate after thawing, the effect of GSH on the cryopreservation of dairy goat semen was explored. Sperm motility parameters were measured with the computer-aided sperm analysis(CASA) system (total power, TM; forward power, PM; linearity, LIN; average path speed, VAP; straight line speed, VSL; curve speed, VCL; beat cross frequency, BCF.). The sperm acrosome integrity rate after thawing was detected by a specific fluorescent probe (isothiocyanate-la beled peanut agglutinin, FITC-PNA), and the sperm plasma membrane integrity rate after thawing was detected by the hypotonic sperm swelling (HOST) method. Reactive oxygen species (ROS) kit, malondialdehyde (MDA) kit, superoxide dismutase (SOD) kit, glutathione peroxidase (GSH-PX) kit were used to detect various antioxidant indicators of thawed sperm. In vitro fertilization experiment was used to verify the effect of adding glutathione on sperm fertilization and embryo development. The results showed that when the concentration of glutathione was 2mmol/l, the sperm viability, plasma membrane intact rate and acrosome intact rate were the highest after thawing, reaching 62.14%, 37.62% and 70.87% respectively, and they were all significantly higher. In terms of antioxidant indexes; the values of SOD and GSH-PX were 212.60 U/mL and 125.04 U/L respectively, which were significantly higher than those of the control group; The values of ROS and MDA were 363.05 U/mL and 7. 02 nmol/L respectively, which were significantly lower than the control group. The addition of 2mmol/L glutathione significantly improves the fertilization ability of sperm. In short, adding 2mmol/l glutathione to the semen diluent can improve the quality of frozen Guanzhong dairy goat sperm.